A case of extensive encircling pulmonary vein isolation in a patient with severe scoliosis. Issue 6 (23rd May 2015) - Kamihara, Takahiro; Kaneko, Shinji; Fujita, Masaya; Yamaguchi, Kazutoshi; Narita, Shingo; Haga, Tomoaki; Hayashi, Daisuke; Ohashi, Taiki; Kubota, Ryuji; Shinoda, Masanori
Abstract: The patient was a 62‐year‐old man with atrial fibrillation and severe scoliosis. Scoliosis may impair cardiorespiratory function. Enhanced computed tomography (CT) was helpful for the Brockenbrough method. Three‐dimensional (3D) mapping also demonstrated clockwise rotation of the heart. We successfully isolated extensive encircling pulmonary vein in this patient using enhanced CT and 3D mapping. The CT venous images revealed appropriate localization of the vein and heart. CT and 3D mapping may ensure a more stable and safer procedure.